Hindcast of Water Level and Flow in the St. Lawrence River Over the 2005–2012 Period. Issue 3 (26th May 2016) - Lefaivre, Denis; D'Astous, Alain; Matte, Pascal
ABSTRACT: A one-dimensional model was run to hindcast water levels and flows for the St. Lawrence River between Montréal and Saint-Joseph-de-la-Rive (100 km east of Québec, Canada). At the upstream boundary, the model uses the flows from Lake Ontario and the Ottawa River basin through lakes Saint-Louis and des Deux-Montagnes and from tributary rivers inside the domain, while at the downstream boundary, it uses water level observations and wind forcing, over the 2005–2012 period. Observations of water level in real time are available at 18 water level gauges but model results provide values at 1061 positions within the domain. The water flow is not measured in real time. Calibration of the model flows provides the ability to issue the flow at the same positions and at the same 3-minute frequency as the water level. Daily flow hindcasts of the St. Lawrence River at Québec over the period is presented. The uncertainties associated with the model results are evaluated using water level and flow observations.